Host-pathogen relationships between the chytrid fungus Batrachochytrium dendrobatidis and tadpoles of five South American anuran species - Arellano, Maria Luz (2017)
The chytrid fungus Batrachochytrium dendrobatidis (Bd) is one of the most important contributors for the decline of amphibian populations worldwide. Evidence indicates that the harmfulness of Bd infection depends on the species and life stage, the fungus strain, the season and environmental factors. In the present paper, we experimentally investigated (i) the susceptibility and sensitivity of five South American tadpole species (Rhinella fernandezae, Scinax squalirostris, Hypsiboas pulchellus, Leptodactylus latrans and Physalaemus fernandezae) to a foreign Bd strain (JEL423), (ii) the response of two populations of P. fernandezae to a native Bd strain (MLA1), and (iii) the virulence of native and foreign Bd isolates on tadpoles of the same species. We also evaluated the relationship between Bd infection and the loss of keratinised mouthparts in P. fernandezae. We found that all species except L. latrans were susceptible to Bd infection with lethal consequences, with R. fernandezae being the most sensitive species. In P. fernandezae, sensitivity to infection depended on population as well as Bd strain, although no relationship was found between fungal infection and the loss of keratinised mouthparts. This is the first experimental study on mortality rates of South American tadpoles exposed to Bd.